Efficiency evaluation of fully integrated on-board EV battery chargers With nine-phase machines - Bodo, Nandor; Levi, Emil; Subotic, Ivan; Espina, Jordi; Empringham, Lee; Johnson, C. Mark (IEEE, 2016)
A fully integrated on-board battery charger for future electric vehicles (EVs) has been recently introduced. It reutilizes all the propulsion components of an EV in charging/vehicle-to-grid (V2G) modes, it does not require any additional components or hardware reconfiguration, and charging/V2G modes are realized with zero electromagnetic torque production. Both fast (three-phase) and slow (single-phase) chargings are possible, with unity power factor operation at the grid side. The solution is based on the use of a triple three-phase machine and a nine-phase inverter/rectifier. This paper reports on the results of efficiency evaluation for the said system. Testing is performed using both a nine-phase induction machine and a nine-phase permanent magnet machine for a range of operating conditions in charging/V2G modes, with both three-phase and single-phase grid connection. Additionally, the impact of converter interleaving on the losses and efficiency is also studied. Losses are separated for different subsystems, thus providing an insight into the importance of optimization of different EV power train components from the efficiency point of view. Promising efficiencies, in the order of 90%, are achieved although none of the system components have been optimized.